2009
DOI: 10.1038/hdy.2009.167
|View full text |Cite
|
Sign up to set email alerts
|

The clock gene cryptochrome of Bactrocera cucurbitae (Diptera: Tephritidae) in strains with different mating times

Abstract: Differences in mating time between populations can give rise to premating reproductive isolation. Tephritid fruit flies exhibit large variation in mating time among intra-or inter-specific populations. We previously cloned the clock gene period from two strains of melon fly, Bactrocera cucurbitae; in one the individuals mate early during the day, whereas in the other the individuals mate later. These strains were originally established by divergent artificial selection for developmental time, 'short' and 'long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 35 publications
3
26
0
Order By: Relevance
“…The negative relationship between circadian period and S-type allele frequency at the cry1212 site is coincident with that observed among the populations from Okinawa (Fuchikawa et al 2010), while no relationship was observed at cry1865. We previously failed to determine which site (cry1212 or cry1865) is responsible for the mating time (Fuchikawa et al 2010).…”
Section: Resultssupporting
confidence: 66%
See 4 more Smart Citations
“…The negative relationship between circadian period and S-type allele frequency at the cry1212 site is coincident with that observed among the populations from Okinawa (Fuchikawa et al 2010), while no relationship was observed at cry1865. We previously failed to determine which site (cry1212 or cry1865) is responsible for the mating time (Fuchikawa et al 2010).…”
Section: Resultssupporting
confidence: 66%
“…We previously failed to determine which site (cry1212 or cry1865) is responsible for the mating time (Fuchikawa et al 2010). In the present study, Taiwan strains exhibited different patterns of combinations of alleles at the sites from the Okinawa strains.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations